Road Traffic Injury–Related Trauma at Abéché University Hospital (Chad): Epidemiological and Injury Patterns - Adoum, Seid Younous; Moussa, Aboulghassim Oumar; Hassan, Adoum Allamine; Guire, Sadié Ismael; Maide, Moussa Kalli; Loukoumi, Oumar Bachar; Sougou, Hemchi Hisseine; Badou, Nazir Ahmat; Ouchemi, Choua (European Scientific Journal, ESJ, 2026)
Objective: To describe the epidemiological profile, injury characteristics, therapeutic management, and outcomes of road traffic accident–related trauma treated at the Abéché University Hospital in eastern Chad. Patients and Methods: This was a retrospective descriptive study conducted over a 12-month period from September 1st, 2023, to August 31, 2024. Results: Among 2,750 consultations, 972 patients were admitted for road traffic injuries, corresponding to a hospitalization rate of 35.34%. The mean age of patients was 26.52 years, with the 21–30-year age group being the most represented (41.60%). Males predominated (82.11%), with a male-to-female ratio of 4.59. Students and pupils constituted the most affected socio-professional group (44.96%). Collisions between tricycles (rakshas) and motorcycles represented the most frequent mechanism of injury (51.7%). The most common lesions were dermabrasions (41.36%) and limb injuries (40.53%), mainly fractures. Head injuries accounted for 4.22% of cases, while polytrauma was observed in 3.60% of patients. Management mainly consisted of local wound care (41.36%), orthopedic treatment (12.65%), and surgical intervention (9.57%). A high rate of discharge against medical advice (24.69%) was observed. The overall in-hospital mortality rate was 9.53%, occurring mainly among patients admitted with severe head injuries and polytrauma. Conclusion: Road traffic accidents constitute a major public health issue in the Abéché province, predominantly affecting young men. Collisions involving tricycles and motorcycles represent the leading cause of injuries and are associated with severe trauma and high mortality. Strengthening road safety measures, improving prehospital medical transport through ambulance services, and upgrading hospital technical infrastructure—particularly intensive care units—are essential to reduce road traffic–related morbidity and mortality.